Proceedings of the 2005 ACM SIGCHI International Conference on Advances in Computer Entertainment Technology 2005
DOI: 10.1145/1178477.1178523
|View full text |Cite
|
Sign up to set email alerts
|

Massive flux design for an interactive water installation

Abstract: This paper identifies and contextualizes the limitations and problems found in interactive installations that require a massive flux of users. It then presents a set of solutions for these practical problems and shows how they have been applied to a real life installation with exceptionally good results. The application is an interactive water installation for children and their families for the international event called "Universal Forum of Cultures, Barcelona 2004".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 2 publications
0
37
0
1
Order By: Relevance
“…This can be achieved by implementing games where multiple players play together, such as interactive playgrounds [11,12], or by explicitly designing interactive installations that target social interactions such as competition [13] or collaboration [14]. To evaluate whether these games achieve their specified goals, questionnaires, observational studies, and interviews are typically used [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by implementing games where multiple players play together, such as interactive playgrounds [11,12], or by explicitly designing interactive installations that target social interactions such as competition [13] or collaboration [14]. To evaluate whether these games achieve their specified goals, questionnaires, observational studies, and interviews are typically used [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…When developing game mechanics to steer behavior it is important to keep the aim, the mechanic, and the measurement aligned. We would like to point out three other things in this discussion: 1) there are some limitations to the study which should be considered, mainly that the collection in itself could be acting as the steering intervention irrespective of its (aesthetical) reward, 2) our ITP seems to be quite suitable for a high throughput of players, what Parés et al [198] indicated with massive flux design, and 3) there are several beneficial aspects of an enticing strategy for steering and opportunities for applying it.…”
Section: Discussionmentioning
confidence: 97%
“…Other systems used a bouncing frame/goal for training handball [108] or soccer [107] 6 . Parés et al created an interactive water installation [196,198]. In this installation players had to create a ring of people and then move around a central fountain, to let water jet into the air in predefined sequences.…”
Section: Fixed Interactive Objectsmentioning
confidence: 99%
See 2 more Smart Citations